Farmyard Manure as K-Fertilizer Modulates Soil Biological Activities and Yield of Wheat Using the Integrated Fertilization Approach - Kumar, Sanjeev; Dhar, Shiva; Barthakur, Sharmistha; Rajawat, Mahendra Vikram Singh; Kochewad, S. A.; Kumar, Sudhir; Kumar, Dileep; Meena, L. R. (Frontiers in Environmental Science, 2021)
Potassium fertilization is often ignored by assuming alluvial soils have sufficient K reserves in the North West Plain Zone of India under cereal-based cropping systems. There is scanty information on the impact of integrated K fertilization on soil enzymes, nutrients availability, microbial population, and wheat yield cultivated in the corn–wheat cropping system. The current study exhibits that treatment (T7) applied with a dose of 90 kg K ha−1 [30 kg K by farmyard manure (FYM) and 60 kg K by muriate of potash (MOP)] significantly enhances the various microbial populations from 48.00 to 123.10% and 39.00 to 124.00%, soil enzymatic activities from 70.31 to 180.00% and 102.42 to 175.68%, and available nutrients from 2.43 to 8.44% and 14.79 to 22.87% for the first and second years of wheat cultivation, respectively. It also improved various yield parameters (12.39–41.71% and 18.24–41.14%) during both the consecutive years of cultivation. Statistical analyses revealed that the treatments (T4, T5, and T7) applied with integrated fertilization of wheat cultivation through FYM and MOP were more promising for improving soil enzymatic activities (11.59–57.22%), microbial populations (5.14–15.70%), available nutrients in soil (7.60–16.54%), and crop yield (1.06–5.85%) during the second year of cultivation as compared to the first year of cultivation. This study might be helpful to reclaim soil health and reduce chemical fertilizers used in agricultural lands.